A receptor‐binding protein of Campylobacter jejuni bacteriophage NCTC 12673 recognizes flagellin glycosylated with acetamidino‐modified pseudaminic acid. Issue 1 (21st November 2014) - Javed, Muhammad Afzal; van Alphen, Lieke B.; Sacher, Jessica; Ding, Wen; Kelly, John; Nargang, Cheryl; Smith, David F.; Cummings, Richard D.; Szymanski, Christine M.
Summary Bacteriophage receptor‐binding proteins (RBPs) confer host specificity. We previously identified a putative RBP (Gp047) from the campylobacter lytic phage NCTC 12673 and demonstrated that Gp047 has a broader host range than its parent phage. While NCTC 12673 recognizes the capsular polysaccharide (CPS) of a limited number of Campylobacter jejuni isolates, Gp047 binds to a majority of C. jejuni and related Campylobacter coli strains. In this study, we demonstrate that Gp047 also binds to acapsular mutants, suggesting that unlike the parent phage, CPS is not the receptor for Gp047. Affinity chromatography and far‐western analyses of C. jejuni lysates using Gp047 followed by mass spectrometry indicated that Gp047 binds to the major flagellin protein, FlaA. Because C. jejuni flagellin is extensively glycosylated, we investigated this binding specificity further and demonstrate that Gp047 only recognizes flagellin decorated with acetamidino‐modified pseudaminic acid. This binding activity is localized to the C‐terminal quarter of the protein and both wild‐type and coccoid forms of C. jejuni are recognized. In addition, Gp047 treatment agglutinates vegetative cells and reduces their motility. Because Gp047 is highly conserved among all campylobacter phages sequenced to date, it is likely that this protein plays an important role in the phage life cycle.